Coverage of Poland’s EU presidency in Romanian printed press and online media – a descriptive analysis - Marinescu, Valentina; Balasescu, Madalina (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
Journalists make use of the main ‘frameworks’of interpretation of the world and of the events which they present in news items and other media products. Professional routines lead journalists to search for information first in sources which have, in their opinion, the power to ‘define’ the situation and to ‘frame’ it. The article analyzes the coverage of Poland’s EU presidency in the Romanian printed press and online media. The analysis was made on a sample of data composed of Romanian articles devoted to Poland’s EU presidency in July 2011–January 2012. The study highlights the similarities in covering Polish presidency of the EU between the Romanian newspapers and online media. At the same time, the results showed that the attention paid by the Romanian mass media to Poland’s EU presidency varied according to the type of media where the article was published: newspapers vs. online media.